2019
DOI: 10.1021/acsptsci.9b00060
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Cystic Fibrosis Transmembrane Conductance Regulator Modulators as New Drugs for Cystic Fibrosis: A Portrait of in Vitro Pharmacology and Clinical Translation

Abstract: Pharmacological correction of the defective ion channel with cystic fibrosis transmembrane conductance regulator (CFTR) has become an attractive approach to therapy directed at the root cause of the life-limiting disease cystic fibrosis (CF). CFTR defects range from absence, misfolding, and resulting degradation to functional defects of the CFTR protein. The discovery and development of the CFTR potentiator ivacaftor was a major break-through in CF therapy and has triggered an enormous incentive for seeking ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 34 publications
0
30
0
2
Order By: Relevance
“…Target for COVID-19? 3 Horm Res Paediatr DOI: 10.1159/000508291 sion and/or specific polymorphisms could play a role, particularly in the lung, and some of the new CFTR modulators should be considered for treatment if this were indeed the case [25,26]. Furthermore, diabetes is a recognized risk factor for Sars-CoV2 infection [27], and HMGB1 is known to be increased in diabetes [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Target for COVID-19? 3 Horm Res Paediatr DOI: 10.1159/000508291 sion and/or specific polymorphisms could play a role, particularly in the lung, and some of the new CFTR modulators should be considered for treatment if this were indeed the case [25,26]. Furthermore, diabetes is a recognized risk factor for Sars-CoV2 infection [27], and HMGB1 is known to be increased in diabetes [8].…”
mentioning
confidence: 99%
“…Finally, my research group previously showed that cystic fibrosis transductance regulator (CFTR) malfunction, as found in cystic fibrosis, increases HMGB1 serum concentrations, along with inflammation, and further increases are observed at the onset of the specifically related diabetes [24]. This suggests that changes in CFTR expression and/or specific polymorphisms could play a role, particularly in the lung, and some of the new CFTR modulators should be considered for treatment if this were indeed the case [25, 26]. Furthermore, diabetes is a recognized risk factor for Sars-CoV2 infection [27], and HMGB1 is known to be increased in diabetes [8].…”
mentioning
confidence: 99%
“…G551D is a missense mutation affecting approximately 4% of the global CF population and causes impaired CFTR channel gating [ 60 ]. Ivacaftor monotherapy approval was later extended to include additional gating mutations, including G1244E, G1349D, G178R, G551S, S1252N, S1255P, S549N, S549R, and R117H [ 7 ]. Ivacaftor (VX-770) targets the dysfunctional CFTR and increases the time in which these channels remain open, allowing for sufficient anion transport ( Figure 7 ).…”
Section: Cftr Modulators and Inflammationmentioning
confidence: 99%
“…The recent development of CFTR modulators, namely ivacaftor, lumacaftor, tezacaftor and elexacaftor, has reinvigorated therapeutic potential of resolving CFTR dysfunction directly as previous treatment options were only targeting secondary manifestations and symptoms [ 7 ]. This review aims to summarise the relationship between CF and lung inflammation, to explore current literature on the anti-inflammatory effects of CFTR modulators, and to propose future research avenues, all aimed to refine our understanding of this life-threatening disease and improve patient outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, researchers are working on different approaches, some of them aimed to handle the basic molecular defect in CF, by restoring proper function to the CFTR protein or correcting its production process so that a normal protein can be build up [50][51][52][53][54], others directed to controlling the clinical manifestations of the diseases, including inflammation, infection and mucociliary clearance, mostly for patients with irreversible lung damage [55][56][57][58][59]. The iminosugar class has representative examples in both fields of application and the results obtained in the last decades have been examined below.…”
Section: Iminosugars In Cystic Fibrosismentioning
confidence: 99%